Blunt abdominal trauma. Retroperitoneal duodenal rupture. - Soto Cordano, José; Belloso García, Rogelio (Cirugía del Uruguay, 1976)
The authors present the case of a 30 years old patient whose abdomen was pressed on by a wagon's wheel. Preoperative diagnosis could be done by the roentgenological study, which showed a right-side retroneumoperitoneum. They performed a duodenal suture and gastroenterostomy, but the patient died after the occurrence of a duodenal fisula.